Konflik Horisontal Gafatar di Kalimantan Barat: Perspektif Johan Galtung - Nikodemus Niko (Nizham Jurnal Studi Keislaman, 2017)
The Presence of Gafatar in West Kalimantan through the transmigration which bring the story of that ended in expulsion of Gafatar. This paper tries to connect the concept of culture violence by Johan Galtung with the stereotyping to the Gafatar. The stereotyping in Gafatar is the flow of astray and dangerous of movement organization, those indicated as trigger of conflict between Gafatar and the local people. This paper uses descriptive approach. This research result indicates that there is a horizontal conflict between civil society, lead to cultural violence. There should have been mapping on the cause and trigger, why conflict happened.